Total Psoas Muscle Area as a Marker for Sarcopenia Is Related to Outcome in Children With Neuroblastoma - Ritz, Annika; Froeba-Pohl, Alexandra; Kolorz, Julian; Vigodski, Victor; Hubertus, Jochen; Ley-Zaporozhan, Julia; von Schweinitz, Dietrich; Häberle, Beate; Schmid, Irene; Kappler, Roland; Lurz, Eberhard; Berger, Michael (Frontiers in Surgery, 2021)
Background: Sarcopenia describes a generalized loss of skeletal muscle mass, strength, or function. Determined by measuring the total psoas muscle area (tPMA) on cross-sectional imaging, sarcopenia is an independent marker for poor post-surgical outcomes in adults and children. Children with cancer are at high risk for sarcopenia due to immobility, chemotherapy, and cachexia. We hypothesize that sarcopenic children with neuroblastoma are at higher risk for poor postoperative outcomes. Patients and Methods: Retrospective analysis of children with neuroblastoma ages 1 to 15 years who were treated at our hospital from 2008 to 2016 with follow-up through March 2021. Psoas muscle area (PMA) was measured from cross-sectional images, using computed tomography (CT) and magnetic resonance imagining (MRI) scans at lumbar disc levels L3-4 and L4-5. tPMA is the sum of the left and right PMA. Z-scores were calculated using age- and gender-specific reference values (https://ahrc-apps.shinyapps.io/sarcopenia/). Sarcopenia was defined as a tPMA z-score below -2. A correlation of tPMA z-scores and sarcopenia with clinical variables and outcome was performed. Results: 164 children with workup for neuroblastoma were identified, and 101 children fulfilled inclusion criteria for further analysis, with a mean age of 3.92 years (SD 2.71 years). Mean tPMA z-score at L4-5 was -2.37 (SD 1.02). Correlation of tPMA z-score at L4-5 with weight-for-age z-score was moderate (r = 0.54; 95% CI, 0.38, 0.66). No association between sarcopenia and short-term outcome was observed. Sarcopenia had a sensitivity of 0.82 (95% CI, 0.62-0.93) and a specificity of 0.48 (95% CI 0.36-0.61) in predicting five-year survival. In a multiple regression analysis, preoperative sarcopenia, preoperative chemotherapy in the NB2004HR group, unfavorable tumor histology, and age at diagnosis were associated with 5-year survival after surgery, with hazard ratios of 4.18 (95% CI 1.01-17.26), 2.46 (95% CI 1.02-5.92), 2.39 (95% CI 1.03-5.54), and 1.01 (95% CI 1.00-1.03) respectively. Conclusion: In this study, the majority of children had low tPMA z-scores and sarcopenia was a risk factor for decreased five-year survival in children with neuroblastoma. Therefore, we suggest measuring the tPMA from presurgical cross-sectional imaging as a biomarker for additional risk stratification in children with neuroblastoma.